Preparation method and application of cross-linked cyclodextrin polymer modified ternary positive electrode material

By modifying the cross-linked cyclodextrin polymer cladding on the surface of the ternary positive electrode material, the stability and conductivity of the material under high temperature or high voltage conditions are solved, and higher electrochemical stability and charge and discharge performance are achieved. .

CN119481018AInactive Publication Date: 2025-02-18SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510052244.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing ternary positive electrode materials are prone to particle breakage under high temperature or high voltage conditions, resulting in capacity deterioration and degradation of cycling performance. At the same time, their inherent conductivity is low, limiting the fast charging and discharging capacity.

Method used

By mixing cyclodextrin with the ternary positive electrode material, dissolving it in a solvent, and adding a crosslinking agent for crosslinking reaction, a crosslinking cyclodextrin polymer coating is formed to modify the ternary positive electrode material.

Benefits of technology

It improves the electrochemical stability and conductivity of the material, weakens the energy attenuation caused by particle breakage, extends the cycle life of the battery, and improves the charge and discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481018A_ABST
    Figure CN119481018A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a cross-linked cyclodextrin polymer modified ternary positive electrode material. The preparation method comprises the following steps: mixing cyclodextrin and a ternary positive electrode material according to a certain proportion, dissolving in a proper solvent, fully stirring for a period of time for the first time, adding a proper amount of cross-linking agent, and continuously stirring at a certain temperature to ensure uniform dispersion; and after the reaction is completed, washing the product with a solvent to remove the unreacted cyclodextrin and cross-linking agent. And drying the washed material in a vacuum drying box to remove the residual solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium batteries, and specifically relates to a preparation method of a cross-linked cyclodextrin polymer modified ternary positive electrode material and its application, especially in an all-solid-state battery. Background Art

[0002] With the rapid development of electric vehicles and renewable energy storage systems, the performance improvement of lithium-ion batteries as key energy storage devices has become particularly important. Among the many battery components, the properties of the positive electrode material directly affect the energy density, cycle life and safety of the battery. However, the currently widely used ternary positive electrode materials (such as nickel cobalt manganese oxide NCM and nickel cobalt aluminum oxide NCA) still face many challenges in terms of high energy density and high power output.

[0003] On the one hand, under high temperature or high voltage conditions, ternary positive electrode materials are prone to particle breakage, resulting in capacity decay and decreased cycle performance. This is caused by structural changes within the material and reactions with the electrolyte, which can lead to failure of the electrode material. On the other hand, many positive electrode materials have inherently low electrical conductivity, especially under high load conditions, which limits their ability to charge and discharge quickly. Although conductivity can be improved by methods such as doping, this often introduces other problems such as increased cost and poor material compatibility. In addition, the interfacial reaction between the positive electrode material and the electrolyte forms a solid electrolyte interface (SEI) film, which leads to increased internal resistance and deterioration of cycle performance. Although some patents have proposed to improve this problem by coating or modification, it is still difficult for existing materials to achieve a long-term stable interface.

[0004] In order to overcome the above problems, several patents have proposed different solutions. For example, some patents use polymer coating technology to enhance electrochemical stability by forming a protective film on the surface of the positive electrode material. However, the chemical resistance and mechanical strength of these films have not yet reached the ideal level, and they may fail under high temperature conditions. In addition, some patents attempt to compound conductive agents with positive electrode materials to improve their conductivity, but this method often leads to a decrease in the overall energy density of the material.

[0005] In view of the above deficiencies in the prior art, the present invention aims to develop a ternary positive electrode material modified with a cross-linked cyclodextrin polymer, which can effectively improve the electrochemical stability and conductivity of the material, thereby solving the problems existing in traditional positive electrode materials. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of a cross-linked cyclodextrin polymer modified ternary positive electrode material in view of the problems existing in the prior art.

[0007] The purpose of the present invention can be achieved by the following scheme: The present invention provides a method for preparing a cross-linked cyclodextrin polymer modified ternary cathode material, comprising the following steps: Cyclodextrin is mixed with the ternary cathode material, dissolved in a solvent, stirred, and then a cross-linking agent is added, and the mixture is stirred and reacted continuously, and filtered to obtain a cross-linked cyclodextrin polymer modified ternary cathode material.

[0008] The obtained cross-linked cyclodextrin polymer modified ternary cathode material is a core-shell structure. The core is the ternary cathode material; the shell is a coating layer (shell) formed by cross-linking reaction of cyclodextrin under the action of a cross-linking agent.

[0009] The present invention uses cyclodextrin polymer to coat the positive electrode material, which has unique advantages compared to the use of other polyaniline (PANI) or acrylate polymers (such as polyacrylic acid, PAA) to coat the positive electrode material, mainly in terms of structural characteristics, stability, functionality, etc. Due to the three-dimensional network properties of its cross-linked structure, cyclodextrin polymer can effectively improve the chemical and thermal stability of electrode materials. For example, cyclodextrin polymer can effectively isolate the positive electrode material from unstable components in the electrolyte through its hydrophilic / hydrophobic properties, reduce side reactions such as oxidation and corrosion, and extend the cycle life of the battery. In addition, cyclodextrin polymer contains a polyrotaxane structure, which can change with the volume of the positive electrode material, while avoiding the powdering of particles to a certain extent.

[0010] Other types of coating materials. For example, polyaniline, although it can provide electrochemical activity as a conductive polymer, may be unstable under high voltage or high temperature environment, degrade or lose conductivity. Acrylate polymers: These polymers tend to absorb water during long-term use, which may affect the overall stability of the battery. And they have poor mechanical strength and thermal stability at high temperatures.

[0011] As an embodiment of the present invention, the cyclodextrin includes β-cyclodextrin and / or γ-cyclodextrin.

[0012] Cyclodextrin molecules have a unique ring structure, in which multiple glucose units are connected to form a hydrophilic outer surface and a hydrophobic inner cavity. This structure enables cyclodextrin to encapsulate small molecules or ions through its inner cavity during the coating process, while interacting with water through its outer surface, and has good biocompatibility and solubility. Conventional organic materials (such as polymers, polyolefins, polyamides, etc.) are usually linear or branched polymer structures, and the internal and external structures do not have the molecular cavity function similar to cyclodextrin.

[0013] A notable feature of cyclodextrin polymers is that they can form inclusion complexes with molecules of different sizes and properties. Cyclodextrin has a specific molecular recognition ability and can encapsulate or stabilize different hydrophobic molecules or metal ions through its ring structure. This property makes the application of cyclodextrin polymers in battery positive electrode materials, especially in enhancing the stability of materials and inhibiting side reactions, have unique advantages.

[0014] Secondly, compared with other polymer coating agents, although the conductivity of cyclodextrin polymer itself is lower, as a coating layer, when the battery is working, the appropriate pore structure in the cyclodextrin polymer can provide a better ion migration path, which helps to improve the battery's charge and discharge performance and efficiency. Cyclodextrin polymers can adjust their porosity and structure through cross-linking reactions, thereby optimizing their ionic conductivity as battery materials. The ionic conductivity of other polymer coating agents, such as polyaniline, usually depends on their doping degree and acid-base environment, and their ion transport performance for batteries is not as good as that of cyclodextrin polymers. Acrylate polymers may provide a certain ionic conductivity, but their pore structure is not as adjustable as that of cyclodextrin polymers, which limits their ion transport efficiency.

[0015] In the present invention, cyclodextrin is used for coating, such as β-cyclodextrin, which is composed of 7 glucose units, forming a larger ring structure with a larger inner cavity space of about 6.0 Å in diameter. Therefore, β-cyclodextrin can coat molecules of larger size. However, α-cyclodextrin, which is composed of 6 glucose units, forms a smaller ring structure with a relatively small inner cavity space of only about 4.7 Å in diameter. When applied to the coating of positive electrode materials, it not only cannot play the role of inner cavity wrapping, but also has limited coating capacity, and its pore structure cannot provide a good ion migration path, and the formed coating layer plays an inhibitory role instead. Relatively speaking, the coating effect of β-cyclodextrin and γ-cyclodextrin is better.

[0016] As an embodiment of the present invention, the ternary positive electrode material includes one or more of NMC811, NCM622, NCM523, NCM712, and NCA.

[0017] As an embodiment of the present invention, the solvent includes one or more of ethanol and water. Water is preferred as the solvent.

[0018] As an embodiment of the present invention, the mass ratio of cyclodextrin to the ternary cathode material is 1-10:100, preferably, more preferably 1-4:100.

[0019] As an embodiment of the present invention, the stirring speed is 300-1000 rpm / min, and the time is 1-3h.

[0020] As an embodiment of the present invention, the cross-linking agent includes one or more of glutaraldehyde and isocyanate.

[0021] The cyclodextrin used in the present invention is a monomer, and the crosslinking agent is an initiator to promote the crosslinking polymerization reaction of cyclodextrin to generate a polymer. These crosslinking agents usually form a three-dimensional crosslinked structure during the polymer synthesis process to enhance the mechanical properties, thermal stability and chemical corrosion resistance of the polymer. However, some crosslinking agents (polyformaldehyde) may react with electrode materials to produce by-products, affecting the performance of the battery. Therefore, when selecting crosslinking agents, it is necessary to ensure that they will not react adversely with the positive electrode material or reduce the efficiency of the battery.

[0022] As an embodiment of the present invention, the mass ratio of the cross-linking agent to the positive electrode material is 2-6:100, preferably 2-4:100.

[0023] As an embodiment of the present invention, the temperature for continuing stirring the reaction is 50-80°C.

[0024] As an embodiment of the present invention, the stirring speed is continued at 600-2000 rpm / min for 6-12 hours.

[0025] As an embodiment of the present invention, the precipitate obtained by filtration is further washed and dried to obtain a cross-linked cyclodextrin polymer modified ternary positive electrode material. The solvent used for washing includes one or more of ethanol and water. The number of washing times is 1-3 times. Drying is vacuum drying at a drying temperature of 60°C.

[0026] As an embodiment of the present invention, the coating thickness of the obtained cross-linked cyclodextrin polymer modified ternary cathode material is 5-10 nm. Excessive use of cyclodextrin and / or cross-linking agent will result in a too thick coating layer, further affecting the ion migration path formed by the pore structure, resulting in the obstruction of Li ion transport, which will in turn reduce battery performance.

[0027] The present invention also provides an application of the cross-linked cyclodextrin polymer modified ternary positive electrode material in an all-solid-state battery.

[0028] The present invention mixes cyclodextrin and ternary positive electrode materials in a certain proportion, dissolves them in a suitable solvent, stirs them for a period of time, adds an appropriate amount of cross-linking agent, and continues to stir at a certain temperature to ensure uniform dispersion. After the reaction is completed, the product is washed with a solvent to remove unreacted cyclodextrin and cross-linking agent. The washed material is dried in a vacuum drying oven to remove residual solvent.

[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) Under high temperature or high voltage conditions, ternary cathode materials are prone to phase change, resulting in capacity decay and decreased cycle performance. The present invention modifies the cathode material by modifying a cross-linked cyclodextrin polymer on the surface of the cathode material, which can change with the volume change of the cathode material, thereby reducing the problem of energy decay caused by particle breakage. After multiple charge and discharge cycles, the capacity retention rate is still very high; (2) Aiming at the problem of low inherent ionic conductivity of positive electrode materials, the present invention modifies a layer of material with high ionic conductivity. Generally speaking, the ionic conductivity of cyclodextrin polymers is 10 -6 S / cm to 10 -4 S / cm, which can improve the Li ion conduction kinetics between the positive electrode and the electrolyte; (3) In order to solve the problem that the interface reaction between the positive electrode material and the electrolyte will form a solid electrolyte interface (SEI) film, which will lead to increased internal resistance and deteriorated cycle performance, the present invention can directly avoid direct contact between the positive electrode active material and the electrolyte material by modifying a layer of cross-linked cyclodextrin polymer on the surface of the positive electrode. By isolating the direct contact between the positive electrode and the electrolyte, the occurrence of side reactions is avoided from the root, thereby improving the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is the TEM spectrum of the cross-linked cyclodextrin polymer modified NCM811 prepared in Example 1; Figure 2 This is the TEM spectrum of the cross-linked cyclodextrin polymer modified NCM811 prepared in Comparative Example 5; Figure 3 This is a 300-cycle charge-discharge cycle diagram of the cross-linked cyclodextrin polymer modified NCM811 assembled full battery prepared in Example 1 at 1.0 C. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0032] The present invention adopts the following steps to test the charge and discharge performance: First, the cross-linked cyclodextrin polymer modified ternary cathode material composite cathode material was prepared: the modified cathode material and the commercially purchased Li6PS5Cl and the purchased commercial conductive fiber were weighed into a zirconia ball mill according to a mass ratio of 70:28.5:1.5. Then the sealed ball mill was fixed on a high-energy planetary ball mill for ball milling. Finally, the molybdate-coated NCM811 composite cathode material was obtained. Then, Li / In was used as the negative electrode and Li6PS5Cl solid electrolyte was used as the electrolyte layer to assemble the all-solid-state battery and test the charge and discharge performance.

[0033] Example 1 Preparation of cross-linked cyclodextrin polymer modified NCM811: NMC811 (100 g) and β-cyclodextrin (2 g) were placed in a 1000 mL eggplant-shaped bottle (650 ml of water) and stirred at 500 rpm / min at room temperature for 2 h. Then, glutaraldehyde crosslinker (2 g) was added to the above solution and stirred at 1000 rpm / min for 10 h. After the reaction was completed, it was filtered and the filter cake was washed three times with ethanol solvent. The washed material was dried in a vacuum drying oven at 60 °C.

[0034] Preparation of cross-linked cyclodextrin polymer modified NCM811 composite cathode material: The modified NCM811 (700 mg), prepared Li6PS5Cl (285 mg) and conductive fiber (15 mg) were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:28.5:1.5. The total mass of the material was 1000 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball milling jar was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours. Finally, a cross-linked cyclodextrin polymer modified NCM811 composite positive electrode material was obtained, such as Figure 1 As shown, the coating layer is about 6nm. Then, Li / In is used as the negative electrode and Li6PS5Cl solid electrolyte is used as the electrolyte layer to assemble the all-solid-state battery and test the charge and discharge performance.

[0035] Application Example 1 Assembly of all-solid-state batteries: Weigh 100 mg of purchased solid electrolyte (Li6PS5Cl) into a 10 mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 180 MPa, then add 10 mg of cross-linked cyclodextrin polymer-modified NCM811 composite positive electrode material on one side of the electrolyte, press it again at a pressure of 360 MPa, then demold it and put it into a special battery test mold, then add a 9 mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium sheet is 30 microns, and the thickness of the indium sheet is 100 microns), and finally install the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it into the battery fixture, and press it at a pressure of 50 MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. Figure 3 As shown, at room temperature and 0.1C rate, the first cycle charging capacity can reach 204mAh / g.

[0036] Example 2 Preparation of cross-linked cyclodextrin polymer modified NCM622: NCM622 (100 g) and β-cyclodextrin (2 g) were placed in a 1000 mL eggplant-shaped bottle (650 ml of water) and stirred at 500 rpm / min at room temperature for 2 h. Then, glutaraldehyde crosslinker (2 g) was added to the above solution and stirred at 1000 rpm / min for 10 h. After the reaction was completed, the filter cake was washed three times with ethanol solvent after filtration and dried in a vacuum drying oven at 60 °C.

[0037] Preparation of cross-linked cyclodextrin polymer modified NCM622 composite cathode material: The modified NCM622 (700 mg), prepared Li6PS5Cl (285 mg) and conductive fiber (15 mg) were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:28.5:1.5. The total mass of the material was 1000 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball mill was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours. Finally, a cross-linked cyclodextrin polymer modified NCM811 composite cathode material was obtained. Then, Li / In was used as the negative electrode and Li6PS5Cl solid electrolyte was used as the electrolyte layer to assemble the all-solid-state battery, and the charge and discharge performance was tested.

[0038] Application Example 2 Assembly of all-solid-state batteries: Weigh 100 mg of purchased solid electrolyte (Li6PS5Cl) into a 10 mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 180 MPa, then add 10 mg of cross-linked cyclodextrin polymer-modified NCM622 composite positive electrode material on one side of the electrolyte, press it again at a pressure of 360 MPa, then demold it and put it into a special battery test mold, then add a 9 mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium sheet is 30 microns and the thickness of the indium sheet is 100 microns), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50 MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitance discharge test. At room temperature and a rate of 0.1C, the first cycle charge capacity can reach 190 mAh / g.

[0039] Example 3 Preparation of cross-linked cyclodextrin polymer modified NCM523: NCM523 (100 g) and β-cyclodextrin (2 g) were placed in a 1000 mL eggplant-shaped bottle (650 ml of water) and stirred at 500 rpm / min at room temperature for 2 h. Then, glutaraldehyde crosslinker (2 g) was added to the above solution and stirred at 1000 rpm / min for 10 h. After the reaction was completed, it was filtered and the filter cake was washed three times with ethanol solvent. The washed material was dried in a vacuum drying oven at 60 °C.

[0040] Preparation of cross-linked cyclodextrin polymer modified NCM523 composite cathode material: The modified NCM523 (700 mg), prepared Li6PS5Cl (285 mg) and conductive fiber (15 mg) were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:28.5:1.5. The total mass of the material was 1000 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball mill was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours. Finally, a cross-linked cyclodextrin polymer modified NCM811 composite cathode material was obtained. Then, Li / In was used as the negative electrode and Li6PS5Cl solid electrolyte was used as the electrolyte layer to assemble the all-solid-state battery, and the charge and discharge performance was tested.

[0041] Application Example 3 Assembly of all-solid-state batteries: Weigh 100 mg of purchased solid electrolyte (Li6PS5Cl) into a 10 mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 180 MPa, then add 10 mg of cross-linked cyclodextrin polymer-modified NCM523 composite positive electrode material on one side of the electrolyte, press it again at a pressure of 360 MPa, then demold it and put it into a special battery test mold, then add a 9 mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium sheet is 30 microns and the thickness of the indium sheet is 100 microns), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50 MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitance discharge test. At room temperature and a rate of 0.1C, the first cycle charge capacity can reach 160 mAh / g.

[0042] Comparative Example 1 The NCM811 composite positive electrode material was prepared by using unmodified NCM811 (700 mg), Li6PS5Cl (285 mg) and conductive fiber (15 mg). The remaining steps were the same as those in Example 1, and the charge and discharge performance was tested. Figure 3 shown.

[0043] Comparative Example 2 The preparation method of this comparative example is basically the same as that of Example 1, except that cyclodextrin is replaced by polyaniline to prepare a coating layer of comparable thickness (the polyaniline coating layer is formed by in-situ polymerization of aniline on the surface of the ternary positive electrode material. The ternary positive electrode material (such as NCM) is dispersed in a solvent. Aniline monomer is added, and the aniline is polymerized in situ by adjusting the pH value and adding a persulfate oxidant. At this time, the polymerization reaction will occur on the surface of the ternary positive electrode material to form a polyaniline coating layer. After the polymerization reaction is completed, the residue is removed by filtrating, washing and drying to obtain a polyaniline-coated positive electrode material).

[0044] Comparative Example 3 The preparation method of this comparative example is basically the same as that of Example 1, except that the glutaraldehyde cross-linking agent is replaced by a paraformaldehyde cross-linking agent.

[0045] Comparative Example 4 Preparation of cross-linked cyclodextrin polymer modified NCM811: NMC811 (100 g) and α-cyclodextrin (10 g) were placed in a 1000 mL eggplant-shaped bottle (650 ml of water) and stirred at 500 rpm / min at room temperature for 2 h. Then, isocyanate linker (10 g) was added to the above solution and stirred at 1000 rpm / min for 10 h. After the reaction was completed, the filter cake was washed three times with ethanol solvent after filtration and dried in a vacuum drying oven at 60 °C.

[0046] Preparation of cross-linked cyclodextrin polymer modified NCM811 composite cathode material: The modified NCM811 (700 mg), prepared Li6PS5Cl (285 mg) and conductive fiber (15 mg) were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:28.5:1.5. The total mass of the material was 1000 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball mill was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours. Finally, a cross-linked cyclodextrin polymer modified NCM811 composite cathode material was obtained. Then, Li / In was used as the negative electrode and Li6PS5Cl solid electrolyte was used as the electrolyte layer to assemble the all-solid-state battery, and the charge and discharge performance was tested.

[0047] Application Example 4 Assembly of all-solid-state batteries: Weigh 100 mg of purchased solid electrolyte (Li6PS5Cl) into a 10 mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 180 MPa, then add 10 mg of cross-linked cyclodextrin polymer-modified NCM811 composite positive electrode material on one side of the electrolyte, press it again at a pressure of 360 MPa, then demold it and put it into a special battery test mold, then add a 9 mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium sheet is 30 microns and the thickness of the indium sheet is 100 microns), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50 MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitance discharge test. At room temperature and a rate of 0.1C, the first cycle charge capacity can reach 110 mAh / g.

[0048] Comparative Example 5 The preparation method of this comparative example is basically the same as that of Example 1 except that the amount of β-cyclodextrin used is 15 g, and the amount of glutaraldehyde crosslinking agent used is 3 g. The obtained cross-linked cyclodextrin polymer modified NCM811 composite positive electrode material is as follows Figure 2 As shown, the coating layer is about 15nm.

[0049] Comparative Example 6 Preparation of cross-linked cyclodextrin polymer modified NCM811: NMC811 (100 g) and α-cyclodextrin (2 g) were placed in a 1000 mL eggplant-shaped bottle (650 ml of water) and stirred at 500 rpm / min at room temperature for 2 h. Then, isocyanate linker (2 g) was added to the above solution and stirred at 1000 rpm / min for 10 h. After the reaction was completed, it was filtered and the filter cake was washed 3 times with ethanol solvent. The washed material was dried in a vacuum drying oven at 60 °C.

[0050] Preparation of cross-linked cyclodextrin polymer modified NCM811 composite cathode material: The modified NCM811 (700 mg), prepared Li6PS5Cl (285 mg) and conductive fiber (15 mg) were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:28.5:1.5. The total mass of the material was 1000 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball mill was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours. Finally, a cross-linked cyclodextrin polymer modified NCM811 composite cathode material was obtained. Then, Li / In was used as the negative electrode and Li6PS5Cl solid electrolyte was used as the electrolyte layer to assemble the all-solid-state battery, and the charge and discharge performance was tested.

[0051] Application Examples Assembly of all-solid-state batteries: Weigh 100 mg of purchased solid electrolyte (Li6PS5Cl) into a 10 mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 180 MPa, then add 10 mg of cross-linked cyclodextrin polymer-modified NCM811 composite positive electrode material on one side of the electrolyte, press it again at a pressure of 360 MPa, then demold it and put it into a special battery test mold, then add a 9 mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium sheet is 30 microns and the thickness of the indium sheet is 100 microns), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50 MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitance discharge test. At room temperature and a rate of 0.1C, the first cycle charge capacity can reach 80 mAh / g.

[0052] The all-solid-state batteries assembled in the embodiments and comparative examples were subjected to charge and discharge performance tests, and the discharge specific capacity and capacity retention rate are shown in Table 1.

[0053] Table 1

[0054] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a cross-linked cyclodextrin polymer modified ternary cathode material, characterized in that: The following steps are involved: Mixing cyclodextrin and ternary cathode material, dissolving in a solvent, adding a crosslinking agent after stirring, continuing stirring to react, filtering, and obtaining a crosslinked cyclodextrin polymer modified ternary cathode material; The obtained cross-linked cyclodextrin polymer modified ternary cathode material is a core-shell structure; the core is the ternary cathode material; the shell is a coating layer formed by cross-linking reaction of cyclodextrin under the action of a cross-linking agent; The cyclodextrin includes β-cyclodextrin and / or γ-cyclodextrin.

2. The preparation method according to claim 1, characterized in that: The ternary positive electrode material includes one or more of NMC811, NCM622, NCM523, NCM712, and NCA.

3. The preparation method according to claim 1, characterized in that: The solvent includes one or more of ethanol and water.

4. The preparation method according to claim 1, characterized in that: The mass ratio of cyclodextrin to the ternary positive electrode material is 1-10:

100.

5. The preparation method according to claim 1, characterized in that: The stirring speed is 300-1000 rpm / min, and the time is 1-3 h.

6. The preparation method according to claim 1, characterized in that: The cross-linking agent includes one or more of glutaraldehyde and isocyanate.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to the positive electrode material is 2-6:

100.

8. The preparation method according to claim 1, characterized in that: The temperature of the continued stirring reaction is 50-80°C; and / or, continuing stirring at a speed of 600-2000 rpm / min for 6-12 h; And / or, the precipitate obtained by filtration is further washed and dried to obtain a cross-linked cyclodextrin polymer modified ternary positive electrode material.

9. The preparation method according to claim 1, characterized in that: The thickness of the coating layer on the obtained cross-linked cyclodextrin polymer modified ternary cathode material is 5-10 nm.

10. Use of the cross-linked cyclodextrin polymer modified ternary cathode material obtained by the preparation method as claimed in claim 1 in an all-solid-state battery.

Citation Information

Patent Citations

  • Silicon-based negative electrode material and preparation method and application thereof

    CN116544385A

  • Sodium battery positive electrode material and preparation method thereof

    CN117766719A

  • Composite positive electrode material coated with slip ring lithium-conducting polymer and preparation method and application of composite positive electrode material

    CN118630160A

  • Composite negative electrode active material and preparation method therefor, negative electrode sheet, secondary battery and electric device

    WO2024087081A1